PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERINTEGRASI INKUIRI TERBIMBING PADA PELAJARAN KIMIA LARUTAN DI SMA KELAS XI UNTUK MENINGKATKAN HASIL BELAJAR KIMIA SISWA - Silalahi, Eka Kartika; Simbolon, Dedi Holden (Unversitas Katolik Santo Thomas, 2025)
This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) model integrated with Guided Inquiry in improving students' chemistry learning outcomes on the topic of solutions among 11th-grade senior high school students. The research was motivated by the low conceptual understanding and critical thinking skills among students, often attributed to the predominance of conventional teaching methods. A quantitative approach with a quasi-experimental design, specifically the non-equivalent control group design, was employed. The participants included two randomly selected classes from SMA Negeri 2 Pematang Siantar: one experimental class (n = 34) and one control class (n = 34). A learning achievement test was used as the main instrument, comprising pre-test and post-test items. The results showed that both groups experienced learning gains; however, the experimental class demonstrated a significantly higher gain score of 0.71 (high category), while the control class achieved a gain score of 0.58 (moderate category). An independent samples t-test revealed a significant difference between the two groups (p = 0.000 < 0.05), indicating that the integrated PBL and guided inquiry model had a substantial impact on students' learning outcomes. These findings suggest that the implementation of PBL integrated with guided inquiry is an effective pedagogical approach to enhance conceptual mastery and should be considered in the teaching of complex chemistry topics.